1989
DOI: 10.1063/1.342816
|View full text |Cite
|
Sign up to set email alerts
|

Performance and failure mechanisms of TiN diffusion barrier layers in submicron devices

Abstract: Defects in reactively sputtered titanium nitride diffusion barriers in submicron devices were investigated. Four different failure mechanisms could be extracted, two originating from the production of the layers, two related to foregoing process steps. The latter are contact hole overetch and topology inside the contact hole, Le., edges, created by deviating isotropic etch ratios of different dielectric layers in a post-treatment after the contact etch. The insufficiencies related to the preparation of the TiN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Titanium nitride LPCVD using TIC14 and NH3 as the source materials has been studied, mainly for hard coatings (4). Recent attempts, including the authors' studies (5)(6)(7)(8)(9)(10), have confirmed the applicability of this method for ULSIs.…”
mentioning
confidence: 91%
“…Titanium nitride LPCVD using TIC14 and NH3 as the source materials has been studied, mainly for hard coatings (4). Recent attempts, including the authors' studies (5)(6)(7)(8)(9)(10), have confirmed the applicability of this method for ULSIs.…”
mentioning
confidence: 91%
“…Because of its exceptional intrinsic properties, such as high hardness, chemical inertness, high electronic conductivity, and low friction coefficient, TiN is applicable in hard coatings, hard cutting-tool inserts, refractory cements, high-temperature materials, and diffusion barriers in very large-scale integrated (VLSI) circuits [1][2][3][4][5][6][7][8][9]. In addition, TiN is widely used as a particulate-reinforced second phase in ceramic composites [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…TiN thin films have been studied and used extensively in recent years due to their superior mechanical, thermal, and electrical properties. [1][2][3] Moreover, it has been suggested that TiN thin films not only serve as buffer layers in depositing superconducting YBa 2 Cu 3 O 7 (YBCO) thin films on various substrates such as Si, Hastelloy, Inconel and stainless steel, but also as the electrode for metallization and integration of superconductor and semiconductor devices. 4,5) In the light of these unique properties exhibited by TiN films, we previously attempted to fabricate the YBCO/TiN/substrate structure by sequential in situ pulse laser deposition (PLD) to investigate the out-of-plate (along c-axis) transport properties of YBCO thin films.…”
mentioning
confidence: 99%